Feasibility of Transcatheter Caval Valve Implantation to Improve Sleep-Disordered Breathing in Patients With Severe Tricuspid Regurgitation—A Pilot Study - Wang, Youmeng; Fernandes Branco, Roberto; Fietzeck, Andrea; Penzel, Thomas; Schöbel, Christoph (Frontiers in Cardiovascular Medicine, 2021)
Transcatheter caval valve implantation (CAVI) has been evaluated as a treatment option for inoperable patients with severe symptomatic tricuspid regurgitation (TR). We studied the effect of CAVI on sleep disorder breathing (SDB) in patients with right heart failure and TR. Twenty right heart failure patients with severe symptomatic TR who underwent portable monitoring of SDB (ApneaLink), echocardiography, cardiopulmonary exercise (CPET), and laboratory testing were enrolled. This was a single-center, nonblinded study. There were no significant changes in sleep variables, echocardiographic parameters, laboratory results, lung function, and CPET after CAVI. In conclusion, these data suggest that CAVI may not have an effect on SDB; however, additional follow-up fully powered studies with appropriate statistical analyses are needed.